Ethical Leadership, Organizational Culture, and Intrapreneurship: A Study in the Banking Sector - DEVECİYAN, MERİ TAKSİ (Nişantaşı Üniversitesi, 2024)
The purpose of this research is to measure the perceptions of bank sector employees regarding ethical leadership, intrapreneurship, and organizational culture, and to examine the relationship between these variables. The cross-sectional survey method was utilized for data collection and analysis, employing quantitative research methods. For this purpose, data collected through surveys from 395 bank personnel using convenience sampling method were evaluated through statistical analyses. The findings indicate a significant positive relationship among bank employees between ethical leadership, organizational culture, and intrapreneurial behavior. It was found that organizational culture has a higher explanatory power for intrapreneurship than the perception of ethical leadership, while ethical leadership has a higher explanatory power for organizational culture. This study provides a significant contribution to understanding the dynamic relationship between ethical leadership, intrapreneurship, and organizational culture. This understanding can guide managers and researchers in leadership strategies and organizational culture development practices. The rarity and significance of this study are underscored by the lack of previous research simultaneously addressing the relationship between ethical leadership, intrapreneurship, and organizational culture in the banking sector, thus indicating its potential to contribute to the academic literature in this field.
Etik Liderlik, Örgüt Kültürü ve İç Girişımcilik: Bankacılık Sektöründe Bir İncelenme
Keywords: Ethical Leadership; Organizational Culture; Intrapreneurship; Banking Sector